Analysis of the mechanism of protein A release and its contribution to immune evasion by Staphylococcus aureus - O'Halloran, Dara (Trinity College (Dublin, Ireland). Department of Microbiology, 2016)
The immunoglobulin binding protein A (SpA) of Staphylococcus aureus was one of the first cell wall-associated proteins of Gram-positive bacteria to be identified and characterised. It is synthesized as a precursor with a C-terminal sorting signal and becomes covalently anchored to the cell wall peptidoglycan by the sortase A enzyme. However, in addition to being displayed on the surface of the bacterium, SpA is also released into the extracellular medium. While cell wall anchored SpA and its role in S. aureus infection has been studied extensively, little is known about how SpA is released or the biological significance of extracellular SpA. LytM is a glycylglycine endopeptidase of S. aureus that was previously shown to promote partial release of SpA from the S. aureus lab strain Newman. Here the influence of LytM on SpA surface-expression and release was analysed in strain Newman and the community-associated methicillin resistant S. aureus (CA-MRSA) strain LAC.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2016